Effect of Percutaneous-Nephrolithotomy on Renal Function Tests and Hemoglobin Levels in the Early Postoperative Period at 24 Hours and 21st Day: PNCL on Renal Function Tests and Hb Levels in the Early Postoperative Period - Hussain, Saddam; Saleem, Muhammad; Ahmad, Farhan; Mahmood, Malik Furqan; Jamil, Muhammad Nasir (Pakistan Journal of Health Sciences, 2026)
The impact of percutaneous nephrolithotomy (PCNL) on renal function tests (RFTs) and hemoglobin (Hb) levels remains debated. Early postoperative changes may indicate transient renal dysfunction and hematological shifts. Objectives: To evaluate measurable changes in serum creatinine, blood urea nitrogen (BUN), estimated glomerular filtration rate (eGFR), and hemoglobin (Hb) following PCNL at 24 hours and 21 days post-procedure. Methods: A detailed case series was conducted at the Department of Urology, Ayub Teaching Hospital, Abbottabad, for exactly three months (2nd August to November 2025). During consecutive sampling, 68 patients aged 18–65 years, ASA Class I–II, subjected to PCNL were included. Renal functions were assessed using eGFR (MDRD formula), while Hb was measured at baseline, 24 hours, and 21 days postoperatively. Repeated-measures ANOVA was performed to analyze within-subject comparisons, while chi-square tests were used for categorical variables. Results: Both eGFR and Hb showed significant declines at 24 hours post-PCNL (64.8 ± 12.9 ml/min/1.73m² and 12.4 ± 2.2 g/dL, respectively; p<0.001 vs. baseline). By day 21, partial recovery (eGFR 69.7 ± 13.1; Hb 13.4 ± 1.9) was noted, showing significantly lower values compared to preoperative levels (p<0.001). Higher eGFR and Hb values were observed in younger patients (18–35 years) across all time points (p<0.05). Conclusions: PCNL produces an initial decline in renal function and hemoglobin levels, with partial recovery by three weeks. Postoperative fluctuations are significantly influenced by age, emphasizing the need for close monitoring in younger patients.